Web-Based Tourism And Culture Information System Using Google Api At The Blora Regency Tourism And Culture Office - Rima Febriana Maryati; Didik Sofian Haryadi; Bambang Suhartono (Journal of Engineering, Electrical and Informatics, 2024)
With the increasingly rapid development of computer technology, internet media is a very effective means of conveying information. Through the internet, various kinds of information from various fields can be obtained quickly. The internet has become an important part as a forum or promotional medium. With the advantages of the internet, the author tries to provide information about the existence of tourism and culture in Blora so that the people of Blora city in particular and people outside the city of Blora in general know it easily and save time. The design of this system was made through several stages. The supporting software used is Apache, Macromedia Dreamweaver MX and PHP as server side-scripting and the final result of this research is a website that provides information about Tourism and Culture of Blora Regency.